PENGARUH KEDUDUKAN DAN MOTIVASI KERJA TERHADAP KEDISIPLINAN KERJA KEPOLISIAN - Mukhammad Bintang Juliano; Noer Mutiara Ningsih, Suci Adelia Salma, Tugimin Supriyadi (CV. Adiba Aisha Amira, 2024)
In the scope of the police, police psychologists are distinctive in relation to the disclosure of cases or case investigations, so there are several professions required of the psychology profession in the police environment. This study aims to analyze the influence of position and work motivation on work discipline in the police environment. Work discipline is an important factor in maintaining the performance and professionalism of police members, work discipline can also affect the effectiveness and efficiency in carrying out their police duties. The presence of psychologists in the scope of the police is expected to help provide support or motivation for work spirit in carrying out their police duties, therefore psychologists play a very important role in the police world. Work motivation is also proven to have a positive and significant impact on police work discipline. A better understanding of the impact of standing in police can help develop more effective management strategies, including leadership training and development. So this research can give us useful insights in understanding the influence of position and motivation on the work discipline of police members.